The Efficacy of Red Ginger Fraction (Zingiber officinale Roscoe var. rubrum) as Insecticidal Aedes aegypti - Chairil Anwar; KM Yahya Syukur; Dalilah Dalilah; Salni Salni; Novrikasari Novrikasari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Aedes aegypti is a vector of Dengue Hemoragic Fever. The use of synthetic chemical insecticide is the most common way to control Ae. aegypti. However, since it can cause resistency if it is used in a wide scale with high frequency and continously, it requires an alternative way. Red ginger (Zingiber officinale Roscoe var. rubrum) is one of natural insecticide which is safe to be used to control Ae. aegypti. This research aims was to determine the activity of active fraction of red ginger to mortality of Ae. aegypti. It was a quasi-experiment research with post test only control design. Twenty Ae. aegypti Liverpool strain were the sample of this research with 5 concentration for each and 4 times repetition. The result showed that concentration 0.5%, 1.0%, 1.5%, 2.0% and 2.5% causing mortality percentage of 32.5%, 33.8%, 51.3%, 58.8% and 65.0% respectively. One way Anova test showed p-value < alpha ± (0.00 < 0.05). It was concluded that there was a significant difference of various concentration of active fraction n-heksan of red ginger extract to the mortality of Ae. aegypti. The lethal concentration (LC50) was 2.409%. It was suggested to continue this research with reppellant or bio-assay test method. Key words: Toxicity, extract, fraction, Aedes aegypti, Insecticidal